HUBUNGAN ANTARA TIMBULNYA PERCERAIAN DENGAN macam pekerjaan suami atau isteri - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
There are many factor may determine whether a marriage will be happy and succesful or not. Among those factors, probably the important is the job of husband or wife. The job could bring them to a tension or anxious situation. Therefore the job of husband or wife may take a role in the failure of marriage. Considering the facts above, the author assumes that there will be a relationship between divorce and the job of husband or wife in married life. The assumption encouraged the author to study the problem. A study of job during married life was carried out in the Yogyakarta, among cases who proposed divorce. Results show that most of the cases of divorce are the private office worker. A comparison between the cases of government employe and private office worker, shows significant differences distribution of divorce.